Examining the Outcomes of Hybrid Coronary Revascularization in Acute STEMI Patients from 2015 to 2022 - Mozhgan Bahramian; Seyed Ali Moezi bady; Maryam Bahramian; Ahmad Amouzeshi (Journal of Interventional Cardiology)
Background. The global rise of chronic diseases, especially cardiovascular disease (CVD), poses a significant public health challenge, being a leading cause of death and disability worldwide. In Iran, the surge in CVD incidence and its risk factors, along with a decrease in the age of onset, has notably increased the reliance on coronary artery bypass grafting (CABG) as a life-saving intervention. Staged hybrid coronary revascularization (HCR), which combines percutaneous coronary intervention with delayed CABG, offers a novel approach for patients with complex coronary artery disease, potentially improving survival and reducing complications. Considering the newness of this treatment method and the limitations of previous studies, we investigated the results of staged HCR in acute ST-elevation myocardial infarction (STEMI) patients in this study. Methods. This observational study was performed on consecutive patients with acute STEMI who underwent staged HCR and were referred to Valiasr and Razi hospitals in Birjand from 2015 to 2022. The required information (demographic information, angiography result, and operation side effects) was collected in a checklist. If necessary, the patients were contacted by phone. After collecting the data, they were entered into SPSS version 16 software. Results. This study was conducted on 33 patients with a mean age of 64.88 ± 9.24 years (69.7% male). The average hospital stay was 11.6 ± 8.9 days (3 to 72 days). The mean ejection fraction and syntax score were 36.5% ± 10.2% and 31.21 ± 6.7, respectively. Following surgery and during hospitalization, arrhythmias were observed, including 33.3% with premature ventricular contractions, 18.1% with atrial fibrillation, and 3.1% with ventricular tachycardia. The average number of pack cells (red blood cells that have been separated for blood transfusion) and creatinine changes before and after hybrid surgery were 640.9 ± 670.9 cc and 0.055 ± 0.07. In the follow-up, 9.09% of patients had late mortality, 6.1% of patients had urinary tract infections during hospitalization, 6.1% of patients had surgical site infections, 3.1% needed dialysis, and none of the studied patients had premature death or need for reintervention. Conclusions. The results of our study indicated that staged HCR performed early after an ACS is not associated with significant mortality or complications. Therefore, it is advisable to consider staged HCR as a surgical option in appropriate cases.